2007
DOI: 10.1186/1471-2164-8-291
|View full text |Cite
|
Sign up to set email alerts
|

Exonization of the LTR transposable elements in human genome

Abstract: Background: Retrotransposons have been shown to contribute to evolution of both structure and regulation of protein coding genes. It has been postulated that the primary mechanism by which retrotransposons contribute to structural gene evolution is through insertion into an intron or a gene flanking region, and subsequent incorporation into an exon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
4
35
0
1
Order By: Relevance
“…similar to those reported for the opossum nPE2 and a consensus CORE-SINE [59% along 70 bp, with a central 45-bp region showing 71% identity (17)], the human ISL1 enhancer and consensus LF-SINE [61% along 55 bp (20)], and the consensus Amn-SINE and human Fgf8 enhancer [70% identity along 170 bp (21)]. Interestingly, a MaLR of the MSTB2 family was recently reported to have been exonized into an alternatively spliced exon of the IL22RA2 gene in primates (34).…”
Section: Discussionmentioning
confidence: 99%
“…similar to those reported for the opossum nPE2 and a consensus CORE-SINE [59% along 70 bp, with a central 45-bp region showing 71% identity (17)], the human ISL1 enhancer and consensus LF-SINE [61% along 55 bp (20)], and the consensus Amn-SINE and human Fgf8 enhancer [70% identity along 170 bp (21)]. Interestingly, a MaLR of the MSTB2 family was recently reported to have been exonized into an alternatively spliced exon of the IL22RA2 gene in primates (34).…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the presence of (1) DNAse1 hypersensitive sites, which mark for accessible chromatin; 36 (2) several histone methylation and acetylation marks, which commonly underlie promoter elements; 37 (3) ESTs, which mark for transcription; 38 and (4) DNA repetitive sequences, which have been shown to impact gene regulation. 39,40 We observed that, for all above-mentioned regulatory features, human cadherin introns displayed similar frequencies in comparison to all non-cadherin introns and to the random data set (P40.05, data not shown), with the exception of DNA repetitive sequences. Human cadherin and non-cadherin introns revealed significant differences in terms of frequency of two specific families of repeats: short interspersed nuclear elements (SINE) and long terminal repeats (LTRs).…”
Section: Selection Of Cadherin Superfamily Membersmentioning
confidence: 78%
“…All these repetitive elements are known to be involved in novel regulatory mechanisms and in exonization. 39,40 Given that the occurrence of exonization leads to the creation of new transcriptionally active regions, we analysed cadherin introns in terms of intron position and observed introns in positions 2 and 3 were not only longer but harboured a concomitant increased frequency of MIR, MaLR and CAGE tags in comparison with the rest of the human genome. This clearly suggests that the long cadherin introns at these two positions may in fact encode novel transcribed regulatory elements associated with MIR and MaLR repetitive elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have analyzed more than 100 arbitrarily isolated HERV LTR sequences, including 5Ј, 3Ј, and solitary LTRs, in a transient-transfection assay and found that about one-third of these LTRs are still active and may drive gene expression (2, 36; S. Weinhardt et al, unpublished data). Thus, HERVs and other LTR retrotransposons represent mobile regulatory modules that may contribute to the transcriptional regulation of cellular genes (5,18,28,33,47). There are a number of bona fide examples for the recruitment of HERV LTRs as transcriptional control elements for cellular genes (for a review, see references 16, 23, and 28), among them LTRs belonging to the multicopy families HERV-H (21, 41) and HERV-L (8,10).…”
mentioning
confidence: 99%